Effect of the oxytocin receptor antagonist nolasiban on pregnancy rates in women undergoing embryo transfer following IVF: analysis of three randomised clinical trials. Issue 4 (4th February 2021) - Griesinger, G; Blockeel, C; Pierzynski, P; Tournaye, , H; Višňová, H; Humberstone, A; Terrill, P; Pohl, O; Garner, E; Donnez, J; Loumaye, E
Abstract: STUDY QUESTION: Does a single oral dose of nolasiban 900 mg administered 4 h before embryo transfer (ET) increase pregnancy rates in women undergoing IVF? SUMMARY ANSWER: In an individual patient data (IPD) meta-analysis of three clinical trials, a single oral dose of nolasiban 900 mg was associated with an increased ongoing pregnancy rate of an absolute 5% (relative 15%). WHAT IS KNOWN ALREADY: Several clinical studies have shown that blocking activation of oxytocin receptors by an oxytocin receptor (OTR) antagonist has the potential to decrease uterine contractions, increase endometrial perfusion and enhance endometrial decidualisation and other parameters of endometrial receptivity. It has been hypothesised that antagonism of oxytocin receptors could improve the likelihood of successful embryo implantation and thus increase pregnancy and live birth rates following ET. STUDY DESIGN, SIZE, DURATION: This is an analysis of three randomised, double-blind, placebo-controlled trials, which randomised 1836 subjects between 2015 and 2019. We describe the results of a meta-analysis of individual participant data (IPD) from all three trials and the pre-specified analyses of each individual trial. PARTICIPANT/MATERIAL, SETTING, METHODS: Participants were patients undergoing ET following IVF/ICSI in 60 fertility centres in 11 European countries. Study subjects were below 38 years old and had no more than one previously failed cycle. They were randomised to a single oral dose of nolasiban 900 mg (n = 846) or placebo (n = 864). In IMPLANT 1, additional participants were also randomised to nolasiban 100 mg (n = 62) or 300 mg (n = 60). Fresh ET of one good quality embryo (except in IMPLANT 1 where transfer of two embryos was allowed) was performed on Day 3 or Day 5 after oocyte retrieval, approximately 4 h after receiving the study treatment. Serum hCG levels were collected at 14 days post oocyte retrieval (Week 2) and for women with a positive hCG result, ultrasound was performed at Week 6 post-ET (clinical pregnancy) and at Week 10 post-ET (ongoing pregnancy). Pregnant patients were followed for maternal (adverse events), obstetric (live birth, gestational age at delivery, type of delivery, incidence of twins) and neonatal (sex, weight, height, head circumference, Apgar scores, congenital anomalies, breast feeding, admission to intensive care and specific morbidities e.g. jaundice, respiratory distress syndrome) outcomes. MAIN RESULTS AND THE ROLE OF CHANCE: In an IPD meta-analysis of the clinical trials, a single oral dose of nolasiban 900 mg was associated with an absolute increase of 5.0% (95% CI 0.5, 9.6) in ongoing pregnancy rate and a corresponding increase of 4.4% (95% CI −0.10, 8.93) in live birth rate compared to placebo. Similar magnitude increases were observed for D3 or D5 transfers but were not significantly different from the placebo. Population pharmacokinetics (PK) demonstrated a correlation between higher exposures and pregnancy. LIMITATIONS, REASON FOR CAUTION: The meta-analysis was not a pre-specified analysis. While the individual trials did not show a consistent significant effect, they were not powered based on an absolute increase of 5% in ongoing pregnancy rate. Only a single dose of up to 900 mg nolasiban was administered in the clinical trials; higher doses or extended regimens have not been tested. Only fresh ET has been assessed in the clinical trials to date. WIDER IMPLICATIONS OF THE FINDINGS: The finding support the hypothesis that oxytocin receptor antagonism at the time of ET can increase pregnancy rates following IVF. The overall clinical and population PK data support future evaluation of higher doses and/or alternate regimens of nolasiban in women undergoing ET following IVF. STUDY FUNDING/COMPETING INTERESTS: The trials were designed, conducted and funded by ObsEva SA. A.H., O.P., E.G., E.L. are employees and stockholders of ObsEva SA. E.L. is a board member of ObsEva SA. G.G. reports honoraria and/or non-financial support from ObsEva, Merck, MSD, Ferring, Abbott, Gedeon-Richter, Theramex, Guerbet, Finox, Biosilu, Preglem and ReprodWissen GmbH. C.B. reports grants and honoraria from ObsEva, Ferring, Abbott, Gedeon Richter and MSD. P.P. reports consulting fees from ObsEva. H.T. reports grants and or fees from ObsEva, Research Fund of Flanders, Cook, MSD, Roche, Gedeon Richter, Abbott, Theramex and Ferring. H.V. reports grants from ObsEva and non-financial support from Ferring. P.T. is an employee of Cytel Inc., who provides statistical services to ObsEva. J.D. reports consulting fees and other payments from ObsEva and, Scientific Advisory Board membership of ObsEva. TRIAL REGISTRATION NUMBERS: ClinicalTrials.gov: NCT02310802, NCT03081208, NCT03758885 TRIAL REGISTRATION DATES: December 2014 (NCT02310802), March 2017 (NCT03081208), November 2018 (NCT03758885) FIRST PATIENT's ENROLMENT: January 2015 (NCT02310802), March 2017 (NCT03081208), November 2018 (NCT03758885).